Behavior of Stabilizing Piles to Increase Stability of Residual Soil Slope - Katman H.Y.B.; Lee C.Y.; Zulnisyam D.U.B.; Pauzi N.I.B.M.; Baharuddin I.N.Z.B. (Roman Science Publications and Distributions, 2024)
-The use of one-row of piles for stabilization of an unstable slope has been employed for many years. However, when one-row of piles are not able to stabilize complex slopes then multiple rows of piles should be adopted. This paper presents the feasibility of using multiple rows of stabilizing minipiles to increase the residual soil slope stability. Consolidated undrained triaxial (CIU) tests were conducted on reconstituted saturated samples of residual soil to determine the shear strength behavior. The response of residual soil slope stabilized with minipiles was carried out using a simplified pile-slope analysis method. The influencing factors on the behavior of residual soil slope stabilized with multiple rows of stabilizing minipiles were investigated. A parametric study was performed for utilizing the use of multiple rows of stabilizing minipiles mainly includes the pile row number, pile row position and slope geometry. The computed stabilizing minipile response shows that the residual soil slope stability with one-row of stabilizing piles is different from that with multiple rows of stabilizing piles. The present study could provide useful insight into the use of multiple rows of minipiles to increase the stability of residual soil slope. Roman Science Publications.